2017
DOI: 10.17886/rki-gbe-2017-123
|View full text |Cite
|
Sign up to set email alerts
|

The health of single mothers and fathers in Germany

Abstract: In every fifth family in Germany, one parent lives alone with children in the household. Life as a single parent is often marked by challenges that include adopting sole responsibility for the child’s education and care, alongside employment commitments, and the difficulties of reconciling work and family life. Moreover, despite comparatively high employment rates, single parents – and their children – are greatly affected by poverty. This paper compares the health of single parents and parents livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 45 publications
(65 reference statements)
1
8
0
Order By: Relevance
“…However, a substantial part of the time effect remains that could not be explained by socioeconomic factors. This finding is consistent with other studies revealing that health disparities in single mothers did not completely disappear after controlling for socioeconomic factors [ 6 , 20 , 32 ]. Previous studies have demonstrated that, in addition to socioeconomic status, the availability of social support, the compatibility of work and family demands, and the relationship with the children as well with the ex-partner are of particular importance for single mothers’ health [ 16 , 33 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, a substantial part of the time effect remains that could not be explained by socioeconomic factors. This finding is consistent with other studies revealing that health disparities in single mothers did not completely disappear after controlling for socioeconomic factors [ 6 , 20 , 32 ]. Previous studies have demonstrated that, in addition to socioeconomic status, the availability of social support, the compatibility of work and family demands, and the relationship with the children as well with the ex-partner are of particular importance for single mothers’ health [ 16 , 33 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have demonstrated that single motherhood is associated with poorer health [ 4 , 5 , 6 , 9 , 10 , 11 , 12 , 31 ]. However, only few studies provide information on the development of health disparities among single and partnered mothers over time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations